Liturgical Theology: Liturgical Inculturation as an Effort to Maintain Religious and Cultural Identity for Catholic Students who are Prospectives Catechists of The Batak Tribe - Tibo, Paulinus; Martasudjita, Emanuel P.D (Universitas Sanata Dharma, 2024)
Local culture has extraordinary wealth for the people who have it and makes life valuable. The existence of local culture is eroded by the presence of outside cultures and becomes consumed by the younger generation, including Catholic students. Cultural changes have also changed for the community, especially students as a young generation. This has an impact on the inculturation of local culture (Batak culture) in the church through Catholic liturgy. This research aims to find out the main elements in the inculturative liturgy, namely aspects of language, building architecture, liturgy music, liturgical clothing, and dance movements, which are cultural artworks that have the values of Batak community life and become an attraction for Catholic students as a form of love for local wisdom. This research uses a descriptive qualitative method with interview techniques for informants, the collection of supporting data through documentation, and direct observation related to the facts that occur about the implementation of liturgical inculturation. Key informants in this research include Catholic students, parish pastoral councils and parishioners, and cultural leaders. The research findings show that Catholic students really understand the basic concept of Catholic liturgical inculturation of local culture in the form of church music, dance, clothing, singing, architectural forms of church buildings, and language. Another finding is that students' love for local culture (Batak culture) in Catholic church liturgy is evidenced by taking part in the celebration of inculturation liturgy. This research shows that Catholic students have an understanding of and love for local culture in the celebration of the inculturation Eucharist.